Force Majeure and Related Doctrines of Excuse in Contract Law of the People’s Republic of China - Ross, Lester (Columbia Journal of Asian Law, 1991)
Since the death of long-time Communist Party Chairman Mao Zedong in 1976, the leaders of the People’s Republic of China (“PRC”) have abandoned the economic policies which had isolated the PRC from the global economy for nearly three decades and have expanded the PRC’s economic interaction with other countries. The Third Plenum of the Eleventh Congress of the Communist Party in 1978 brought to power reform-minded officials who had a greater appreciation of market practices.’ Deng Xiaoping, who became the paramount leader at that time, led a movement within the highest reaches of the Communist Party (the “Party”) that, while not forsaking centralized planning, reoriented both the Party and the PRC in favor of a significantly more decentralized, market-oriented, incentive-based economy much more open to international trade. As part of a larger plan of expanding the PRC’s private sector to meet market demands, these reformers sought to increase the PRC’s involvement in interna- tional trade and to encourage foreign investment in China. Foreign businesses, excited by this new “open door” policy, increased their trade With and investment in the PRC.